1991
DOI: 10.3171/jns.1991.74.6.0979
|View full text |Cite
|
Sign up to set email alerts
|

Nucleolar organizer regions in various human brain tumors

Abstract: Nucleolar organizer regions (NOR's) are loops of deoxyribonucleic acid (DNA) which transcribe to ribosomal ribonucleic acid (RNA) by RNA polymerase I. They possess vital significance in the ultimate synthesis of cellular proteins. A silver colloid staining technique for demonstration of NOR-associated proteins (Ag-NOR's) was applied to paraffin-embedded sections from 128 varied brain tumors and to chromosomal preparations from cultured brain-tumor cells. There was a statistically significant difference in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

1991
1991
2005
2005

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…Detailed discussions on the methodology of PCNA [13,14,26] and AgNORs [10,15,25] are given elsewhere. Comparison of the results of this study with those reported in literature on the PCNA index [17] and AgNOR index [9,24,28] in meningioma, showed that the values for NON and benign meningiomas were almost equal. Comparison of the results of this study with those reported in literature on the PCNA index [17] and AgNOR index [9,24,28] in meningioma, showed that the values for NON and benign meningiomas were almost equal.…”
Section: Discussionsupporting
confidence: 67%
“…Detailed discussions on the methodology of PCNA [13,14,26] and AgNORs [10,15,25] are given elsewhere. Comparison of the results of this study with those reported in literature on the PCNA index [17] and AgNOR index [9,24,28] in meningioma, showed that the values for NON and benign meningiomas were almost equal. Comparison of the results of this study with those reported in literature on the PCNA index [17] and AgNOR index [9,24,28] in meningioma, showed that the values for NON and benign meningiomas were almost equal.…”
Section: Discussionsupporting
confidence: 67%
“…If correctly applied, the AgNOR technique should allow a good evaluation of the cell cycle time. By way of a reminder, nucleolar organizer regions are loops of DNA that are transcribed to RNA by RNA polymerase I, and are of vital signi®cance in the ultimate synthesis of cell proteins (Shiraishi et al 1991). These NOR can be histochemically revealed by means of argyrophilic (Ag) staining (hence the AgNOR designation).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, some markers use the speed with which cycling cells produce daughter cells. The argyrophylic nucleolar organiser region (AgNOR) technique could be used for this kind of marker (Bigras et al 1996;Carbajo et al 1993;Maier et al 1990;O È fner et al 1992;Shiraishi et al 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Within the last lew yeais, AgNOR staining has been used to study cutaneotis neoplasms (16, 26) and other solid tumors, including breast (33), prostate (34), brain (35,36), liver (22), and colon carcinomas (23), lymphomas (27), and osteogenic sarcomas (37). In 1987, Crocker et al (1) published their sttidies cm AgNOR counts in cntaneons melanocytic lesions and showed a significant difference between nevi (mean 1.2/nucletis) and cutaneous melanoma (mean 7.9/nticlens).…”
Section: Discussionmentioning
confidence: 99%